The Extent to Which Charity Organization Benefit From Bank Interests - Alsawa, Ali Mohammad; Almousa, Nusaiba Ali; Alsori, Kefah (Dirasat: Shari'a and Law Sciences, 2023)
Objectives: The study amid at clarifying the way of dealing with the issue of conventional bank interests and the extent to which charities and non-profit organizations may benefit from it in their projects. Methods: The research follows the descriptive analytical comparative approach, which has been achieved through the induction of relevant jurisprudential evidences, and the perspective of the old and contemporary jurists, then analyzing their opinions, in order to conclude the preponderant. Results: The bank interests are considered as kind of unlawful usury as per the all contemporary jurists’ groups and individuals. Moreover, the money gained from usury is unlawful to be used for personal or family spending. Adding to that, such kind of money should be spent on poor people and charities. Conclusions: Prohibiting the traditional bank interests, and using them for personal or family interest. However, recommending usury beneficiaries to donate interest amounts for charities and non-profit organizations